ҚАРАҚАЛПАҚ ХАЛЫҚ ПЕДАГОГИКАСЫНДА БАЛАЛАРДЫҢ ЛОГИКАЛЫҚ ОЙЛАЎЫН ЖЕТИЛИСТИРИЎДЕ ЖУМБАҚЛАР ҲӘМ ХАЛЫҚ АЎЫЗ-ЕКИ ДӨРЕТПЕЛЕРИНИҢ ӘҲМИЙЕТИ - Ибрагимова, Л.А. (FAN va JAMIYAT, 2022)
The article deals with one the most important problems of bringing up school children and the influence of works of Karakalpak folklore as fairy tales, riddles, twisters, proverbs and sayings, children's poem's and phymes onto children's psychology. Thein educational role are keveled on the bage of theoretical and historical aspects of pedagogics.